Complete ultrafast charge carrier dynamics in photo-excited all-inorganic perovskite nanocrystals (CsPbX3). Issue 5 (17th January 2017) - Mondal, Navendu; Samanta, Anunay
Abstract : The spectral and temporal characterization of the ultrafast transients of CsPbX3 nanocrystals and the effect of halide substitution on the dynamics of carrier cooling and trapping are studied through femtosecond pump–probe and fluorescence up-conversion techniques. Abstract : Understanding the nature and dynamics of the photo-induced transients of all-inorganic perovskite nanocrystals (NCs) is key to their exploitation in potential applications. In order to determine the nature of charge carriers, their deactivation pathways and dynamics, the photo-induced transients of CsPbBr3, CsPbBr2 I, CsPbBr1.5 I1.5 and CsPbI3 NCs are spectrally and temporally characterized employing a combination of femtosecond transient absorption (TA) and photoluminescence (PL) up-conversion techniques and global analysis of the data. The results provide distinct identities of the excitons and free charge carriers and distinguish the hot charge carriers from the cold ones. The carrier trapping is attributed to the electrons and their dynamics is unaffected in mixed halide perovskites. The excitation energy dependence of the TA dynamics suggests that the trap states are shallow in nature and mainly limited near the band-edge level. In mixed halide perovskites, an increase in the iodine content leads to hole trapping in a short time scale (<5 ps). The insights obtained from this study are likely to be helpful for tuning the photo-response of these substances and their better utilization in light-based applications.